Genetic typing of Vibrio cholerae strains biovar El Tor isolated from the Caucasus region during the 1970–1998 period using MLVA-5 and wgSNP - D. A. Kovalev; N. A. Shapakov; S. V. Pisarenko; I. V. Savel’eva; O. V. Vasil’eva; V. N. Savel’ev; Yu. V. Siritsa; A. M. Zhirov; D. V. Ul’shina; I. V. Kuznetsova; O. V. Bobrysheva; A. N. Kulichenko (Журнал микробиологии, эпидемиологии и иммунобиологии, 2021)
Aim. Our aim was to perform phylogenetic analysis of Vibrio cholerae O1 El Tor biovar strains, isolated from the Caucasus region over the years, using MLVA and wgSNP methods.Materials and methods. We studied genomic sequences of 16 clinical V. cholerae O1 strains of El Tor biovar isolated on the territory of Caucasus from 1970 to 1998. These strains were obtained from the State Collection of Pathogenic Microorganisms of Stavropol Plague Control Research Institute. 87 whole genome sequences of V. cholerae strains, obtained from NCBI database, were also included in the analysis. MLVA-typing was carried out at 5 VNTR-loci. Whole genome sequencing was performed on Ion Torrent PGM platform.Results. We determined that the studied strains belong to 15 MLVA-types and are divided in 3 groups of 1 cluster. We performed an analysis of the structure of the main virulence and pathogenicity islands, as well as nucleotide polymorphisms in ctxB, tcpA, RstR genes. We performed a wgSNP-based phylogenetic analysis of the strains, and described SNPs, specific for each phylogenetic group.Conclusion. We confirmed the polyclonal origin of genetically modified variants of V. cholerae O1 biovar El Tor. We determined the place of V. cholerae strains of biovar El Tor, isolated from 1970 to 1998 on the territory of the Caucasus, in the global population of the pathogen. It is shown that during this period, strains belonging to the first and second waves of the seventh cholera pandemic circulated within the Caucasus. It was confirmed that cases of cholera in the Caucasus were imported from the territory of endemic countries, and the most probable sources of infection were identified.